THE EFFECT OF THINK TALK WRITE (TTW) STRATEGY AND STUDENTS’ READING HABIT TOWARD STUDENTS’ WRITING ABILITY - Heny Ambarsari; Hermawati Syarif; Refnaldi Refnaldi (Universitas Negeri Padang, 2018)
The purpose of this research was to find out the effect of Think-Talk-Write Strategy and students’ reading habit toward students’ writing ability of report text. The design of this research was quasi experimental with 2x2 factorial design. The population of this research was the third grade students of SMP IT Al-Husna Kampar Riau. The technique that was used in selecting the sample was cluster random sampling. The sample of his research was IX C as the experimental research and IX D as the control class. Writing test and reading habit questionnaire were used as the research instruments. Furthermore, the data were analyzed by using t-test formula and two ways Anova. The finding showed that Think-Talk-Write Strategy gives significant effect on students’ writing ability as compared to Listing Strategy especially for students with high reading habit as compared to Listing Strategy. The result of two ways Anova showed that there is no interaction between strategy used and reading habit toward students’ writing ability.